3D-printed constructs deliver bioactive cargos to expedite cartilage regeneration - Rong Jiao; Xia Lin; Jingchao Wang; Chunyan Zhu; Jiang Hu; Huali Gao; Kun Zhang (Journal of Pharmaceutical Analysis)
Cartilage is solid connective tissue that recovers slowly from injury, and pain and dysfunction from cartilage damage affect many people. The treatment of cartilage injury is clinically challenging and there is no optimal solution, which is a hot research topic at present. With the rapid development of 3D printing technology in recent years, 3D bioprinting can better mimic the complex microstructure of cartilage tissue and thus enabling the anatomy and functional regeneration of damaged cartilage. This article reviews the methods of 3D printing used to mimic cartilage structures, the selection of cells and biological factors, and the development of bioinks and advances in scaffold structures, with an emphasis on how 3D printing structure provides bioactive cargos in each stage to enhance the effect. Finally, clinical applications and future development of simulated cartilage printing are introduced, which are expected to provide new insights into this field and guide other researchers who are engaged in cartilage repair.